Using anti-war art to create and build cultures of peace in the classroom and beyond - Castellani, Eladia; Dabove, Claudia; Guzmán, Patricia Fabiana (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The aim of this proposal is to work in an interdisciplinary project involving the subjects Language and Culture (or Social Studies) and EFL Teaching (or Didactics) in a teacher training college. The former subjects deal with the historical and cultural aspects of the 18th, 19th and 20th centuries whereas the latter provides the methodological background for teaching English as a foreign language. These subjects provide an appropriate context in which to work with human rights in the analysis of significant works of art in the historical periods. Finally, the proposal suggests an extracurricular activity for the local community.